Development of Wireless Endoscope with Symmetrical Motion Characteristics. (17th September 2014) - Guo, Jian; Guo, Shuxiang; Wei, Xiang; Wang, Yunliang
In the biomedical field, a wireless microrobot in a pipe which can move smoothly in water or other aqueous mediums has been urgently demanded. In this paper, several methods of designing a novel microrobot with symmetrical motion characteristics have been discussed and a new kind of wireless microrobot has been developed. According to the modelling analysis, we considered two kinds of common cases occurring in vertical motion, which required gravity compensation. Based on two groups of simulations and experiments on forward-backward motion, upward-downward motion and inclined plane motion, the results and dynamic error evaluation indicated that the wireless microrobot with symmetrical structure could realize similar kinematic characteristics in the horizontal motion. The gravity compensation played an important role in the design process, and the performance of the vertical motion had been improved by gravity compensation. With this method, we made the wireless microrobot realize symmetrical motion characteristics, and simplified the control strategies. Finally, a control panel for our system was designed, which could control the current motion states more intuitively and far more easily through the buttons. The developed wireless microrobot would be very useful in the industrial application and microsurgery application.